Maqashid al-Shariah as the Foundational Framework for Strengthening Islamic Economic Regulation in Indonesia - Munir, Misbachul (STAI Miftahul Ula Nganjuk, 2025)
Abstract: The development of Islamic economics in Indonesia requires regulatory reinforcement that transcends formal legality and embodies the substantive values of Islamic law. Maqashid al-Shariah, with its five essential objectives protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-‘aql), lineage (hifz al-nasl), and wealth (hifz al-mal) offers an ideal paradigm for achieving maslahah (public welfare) within the Islamic economic system. This study aims to analyze the implementation of Maqashid al-Shariah principles in Indonesia’s Islamic economic regulations, while identifying key challenges and opportunities for integration. Employing a qualitative library research design, this study draws on both primary sources (laws, OJK and BI regulations, DSN-MUI fatwas) and secondary sources (books and peer-reviewed journal articles). Data were analyzed using content analysis to assess the extent to which current regulations reflect maqashid principles. The findings reveal that although Indonesia’s Islamic economic regulations have partially adopted maqashid values particularly in Shariah compliance (hifz al-din) and wealth protection (hifz al-mal) their implementation remains suboptimal. Major obstacles include regulatory fragmentation, limited financial literacy (hifz al-‘aql), and the dualism between secular and religious legal systems. Despite these challenges, the study highlights significant opportunities for reform, particularly through the establishment of a Comprehensive Islamic Economic Framework Law explicitly grounded in Maqashid al-Shariah. The research concludes that a more substantive, maqashid-based integration beyond formal legalism can revitalize Indonesia’s Islamic economic system toward inclusive, just, and sustainable growth aligned with global ethical finance trends.